2002
DOI: 10.1097/00005392-200206000-00036
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction With the Outcome of Surgery for Urethral Stricture

Abstract: Patients consider the outcome of surgery for urethral strictures differently than physicians. The outcome of urethroplasty should be assessed not only by objective, but also by subjective criteria. Patients need appropriate preoperative counseling. With realistic expectations most men are satisfied with surgery for urethral stricture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…Possible explanations for postoperative postvoid dribbling are stricture recurrence, damage to the M.bulbospongiosum and/or sacculation of the graft. In the study of Kessler et al, postoperative postvoid dribbling was even present in 58.9% of the patients (9).…”
Section: Ici-q-sfmentioning
confidence: 89%
See 2 more Smart Citations
“…Possible explanations for postoperative postvoid dribbling are stricture recurrence, damage to the M.bulbospongiosum and/or sacculation of the graft. In the study of Kessler et al, postoperative postvoid dribbling was even present in 58.9% of the patients (9).…”
Section: Ici-q-sfmentioning
confidence: 89%
“…The only dissatisfied patient in this series was because of a postoperative fistula. It has been reported that postoperative complications might have an influence on the patient satisfaction (9). The other 20 patients were satisfied by the operation despite some functional disturbances (erectile dysfunction, urge-incontinence, post-void dribbling).…”
Section: Patient Satisfactionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies by Palminteri et al, 12 Shenfeld et al, 13 Kessler et al, 14 Anger et al 15 and Nelson et al 16 concluded that there …”
Section: Discussionmentioning
confidence: 99%
“…As for bulbar urethra stricture, removal of bulbar urethral stricture scar using narrow segment anastomosis has shown satisfactory results [10]. However, using the above treatments in penile urethra stricture may result in penile shortening, painful erection, etc., and thus, their clinical use is minimal [11]. Meanwhile, the traditional treatments such as urethral dilation and cold knife urethrotomy have higher recurrence rates which also results in limited clinical application.…”
Section: Discussionmentioning
confidence: 99%